Circulating MIF Associated With Disease Severity and Clinical Response of Sublingual Immunotherapy in House Dust Mite–Induced Allergic Rhinitis - Xie, Shaobing; Zhang, Hua; Wang, Fengjun; Xie, Zhihai; Jiang, Weihong; Gao, Kelei (Frontiers in Pharmacology, 2021)
Background: Macrophage migration inhibitory factor (MIF) is described as a pro-inflammatory cytokine involved in many inflammatory and allergic disorders, but the role of MIF in allergic rhinitis (AR) remains poorly clarified. The aim of this study is to investigate the association between circulating MIF levels and house dust mite (HDM)- induced AR, and evaluate MIF as a potential biomarker in reflecting disease severity and predicting the clinical response of sublingual immunotherapy (SLIT) in HDM-induced AR patients. Methods: In this study, we enrolled 160 persistent HDM-induced AR patients (AR group), including 48 mild AR patients (MAR group) and 112 moderate-severe AR patients (MSAR group), and 77 healthy controls (HC group). Circulating levels of MIF were measured by ELISA, and the relationship between MIF concentrations and disease severity was assessed. In the MSAR group, 106 patients were assigned to receive SLIT for 3 years. At the end of study, patients were categorized into good response group and poor response group, and associations between clinical variables or biomarkers and clinical response were analyzed by multivariate regression analysis. Results: The concentrations of serum MIF were significantly higher in AR patients than HCs, especially in those with MSAR. Moreover, circulating MIF levels were positively correlated with TNSS, VAS, serum HMD specific IgE, total IgE, blood eosinophil count and blood eosinophil percentage, respectively (all P<0.05). Eighty MSAR patients finally completed SLIT, 45 patients obtained good response and 35 patients resulted in poor response. The serum levels of MIF were significantly lower in good response group than in poor response group (P < 0.001). Receiver operating characteristic analysis for MIF showed good accuracy for predicting clinical response of SLIT (area under the curve = 0.877, P<0.001). Multivariate regression analysis demonstrated that serum MIF was an independent factor for SLIT responsiveness. Conclusion: Serum MIF appeared to be an important biological indicator in reflecting disease severity and an independent predictor for clinical responsiveness of SLIT in HDM-induced AR patients.